Peroxiredoxin-6 Negatively Regulates Bactericidal Activity and NF-κB Activity by Interrupting TRAF6-ECSIT Complex - Min, Yoon; Wi, Sae M.; Shin, Dongwoo; Chun, Eunyoung; Lee, Ki-Young (Frontiers in Cellular and Infection Microbiology, 2017)
A TRAF6-ECSIT complex is crucial for the generation of mitochondrial reactive oxygen species (mROS) and nuclear factor-kappa B (NF-κB) activation induced by Toll-like receptor 4 (TLR4). Peroxiredoxin-6 (Prdx6) as a member of the peroxiredoxin family of antioxidant enzymes is involved in antioxidant protection and cell signaling. Here, we report on a regulatory role of Prdx6 in mROS production and NF-κB activation by TLR4. Prdx6 was translocated into the mitochondria by TLR4 stimulation and Prdx6-knockdown (Prdx6KD) THP-1 cells had increased level of mitochondrial reactive oxygen species levels and were resistant to Salmonella typhimurium infection. Biochemical studies revealed Prdx6 interaction with the C-terminal TRAF-C domain of TRAF6, which drove translocation into the mitochondria. Interestingly, Prdx6 competitively interacted with ECSIT to TRAF6 through its C-terminal TRAF-C domain, leading to the interruption of TRAF6-ECSIT interaction. The inhibitory effect was critically implicated in the activation of NF-κB induced by TLR4. Overexpression of Prdx6 led to the inhibition of NF-κB induced by TLR4, whereas Prdx6KD THP-1 cells displayed enhanced production of pro-inflammatory cytokines including interleukin-6 and -1β, and the up-regulation of NF-κB-dependent genes induced by TLR4 stimulation. Taken together, the data demonstrate that Prdx6 interrupts the formation of TRAF6-ECSIT complex induced by TLR4 stimulation, leading to suppression of bactericidal activity because of inhibited mROS production in mitochondria and the inhibition of NF-κB activation in the cytoplasm.